Images of rupture between East and West: the perception of Auschwitz and Hiroshima in Eastern European arts and media - Heftrich, Urs; Jacobs, Robert A.; Kaibach, Bettina; Thaidigsmann, Karoline (Beiträge zur neueren Literaturgeschichte, 2016)
In spite of the incommensurability of the Holocaust and the dropping of the first atomic bombs, the juxtaposition of Auschwitz and Hiroshima has long been a topic of serious debate. However, the fact that the interpretation of the two events in Eastern Europe differed considerably from the Western angle was largely neglected. While in Western thinking, both Auschwitz and Hiroshima were often seen as ruptures that shook the foundations of civilization, in communist Eastern Europe the concept of rupture was either ignored or dismissed as Western defeatism. In their contributions, international scholars investigate the perception of Auschwitz and Hiroshima in Eastern Europe from a wide range of disciplines. The volume presents a complex picture of the divides and intersections between different cultures of commemoration, including American and Japanese responses to Auschwitz and Hiroshima
"Conference, entitled "Images of ruptures in civilization between East and West. The iconography of Auschwitz and Hiroshima in Eastern European arts and media" (Bilder des Zivilisationsbruchs zwischen Ost und West. Die Ikonographie von Auschwitz und Hiroshima in den Künsten und der Publizistik Osteuropas), was hosted by Internationales Wissenschaftsforum Heidelberg from 26-29 May 2011. All essays included in this volume, with the exception of Tvrtko Jakovina's contribution, were originally presented at the Heidelberg conference." - Introduction, Seite 11
Keywords: Auschwitz (Concentration camp) -- In art; Hiroshima-shi (Japan) -- In art; Aufsatzsammlung; Konferenzschrift -- 2011 -- Heidelberg; Atombombenabwurf auf Hiroshima; Konzentrationslager Auschwitz; Geschichte 1945-2000; Osteuropa; Massenmedien; Künste; Rezeption; Judenvernichtung